A Study of Profitability Analysis with Reference to Selected Cement Companies in India: A Comparative Analysis of Profitability in the Indian Cement Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objective of this study is to investigate the impact on firm's profitability through the selected cement companies in India.Primary motive of any business is to make profit. Profitability is nothing but ability of an investment to earn return from its use. The study is based on secondary data i.e. eight years financial statements collected from Moneycontrol and Annual reports. Based on operating profit, Net profit Ratio and Net worth.Cement industry is a largest industry in world economy and Indian cement industries is second largest in the world. It plays an important role in providing employment, infrastructure and housing sector, it attracted FDI worth US 5.28 billion during the year April 2000 to December 2018. The production capacity is projected to reach 550-600 million tonnes per annum (MTPA) by 2025. The housing sector is the biggest demand driver of cement, accounting for about 67 per cent of the total consumption in India. The research paper mainly focuses on analyses of profitability of selected cement companies in India during period of 2011 to 2018, Profitability shows the Business and Financial efficiency of a business concern as well it also attracts Investors. It is an important instrument to measure not only the business performance but also overall efficiency in its concerned. In present study varioustools used for analysis are mean, standard deviation, co-efficient of variation and compound annual growth rate. The study reveals that the profitability position of JK cements is satisfactory when compare to other companies like ACC Cement, Ambuja Cement, India Cement and Ultratech Cement.